Design and synthesis of novel methoxypyridine-derived gamma-secretase modulators. Issue 22 (15th November 2020) - Rynearson, Kevin D.; Buckle, Ronald N.; Herr, R. Jason; Mayhew, Nicholas J.; Chen, Xinchao; Paquette, William D.; Sakwa, Samuel A.; Yang, Jinhai; Barnes, Keith D.; Nguyen, Phuong; Mobley, William C.; Johnson, Graham; et al.
Graphical abstract: Abstract: The evolution of gamma-secretase modulators (GSMs) through the introduction of novel heterocycles with the goal of aligning activity for reducing the levels of Aβ42 and properties consistent with a drug-like molecule are described. The insertion of a methoxypyridine motif within the tetracyclic scaffold provided compounds with improved activity for arresting Aβ42 production as well as improved properties, including solubility. In vivo pharmacokinetic analysis demonstrated that several compounds within the novel series were capable of crossing the BBB and accessing the therapeutic target. Treatment with methoxypyridine-derived compound 64 reduced Aβ42 levels in the plasma of J20 mice, in addition to reducing Aβ42 levels in the plasma and brain of Tg2576 mice.